Food security and policy responses with special reference to the poultry industry - Shamsudin, Mad Nasir (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
The right to food is the basic tenet of the food security policy of any nation. The guiding framework is based on the World Food Summit 1996 interpretation which stated that: food security as existing when all people, at all times, have physical and economic access to sufficient, safe and nutritious food that meets their dietary needs and food preferences for an active and healthy life (FAO, 2003). Most developing economies had translated their food security drive by a number of policy measures to ensure availability, accessibility, and utilisation. The food security agenda in the twenty-first century faces a totally new set of challenges. Domestically, the competition for resources (land, labour and capital) continues to intensify as urbanisation and industrialisation grow rapidly. Limited investment in food and agriculture have made this sector lagged on all fronts; productivity, efficiency and development. The effect of climate change is showing, aggravated further by unsustainable practices such as overuse of chemical fertilisers, and poor water management. The international market also poses the bigger challenge to developing countries’ food security in particular “extreme volatility”. The course of the global food system is no longer in the main determined by the resolution of demand and supply fundamentals. External shocks are emerging from a complexity of sources and are having a profound influence in causing vulnerability in food systems. The detrimental impact of volatility is further magnified by structural problems such as: poor infrastructure, poor supply response, inefficient market, and susceptibility to climactic disturbances. Malaysia is self-sufficient in some of the food commodities such as poultry meat (128%), eggs (115%), pork (102%), and fisheries (102%). However, she is not self-sufficient in commodities such as rice (71%), fruits (66%), vegetables (41%), beef (29%), mutton (11%) and dairy milk (5%) (MOA, 2010). The food trade deficit grows from year to year, from RM1 billion (US$0.33 billion) in 1990 to RM12 billion (US$ 4 billion) in 2011 (DOS, 2011). Like any other developing countries, Malaysia has enjoyed the benefits of cheaper food imports. This dependence however has its price as it disincentivised the country to seek ways and means to improve productivity and efficiency. Although the country is self-sufficient in poultry meat, there are still pertinent issues with regards to production sustainability, accessibility and utilisation, particularly food safety. The production is mainly based on imported feed. The share of food price to the overall consumer price index is 30.3% which indicates little margin for changes in food prices. Efforts to improve food safety, which is a market failure, must be evaluated in terms of their impact on additional costs and returns to producers, risk reduction, economic gains for the domestic industry, and positive spillovers for food safety in the domestic food system. To the extent that the externality costs are borne by society, it is unlikely that the supply and demand functions will fully embody the economic consequences of the consumption of the food. In the National Agro-food Policy (2011–2020), the overall objective with respect to the poultry industry is to improve productivity and competitiveness to ensure food security for the nation and increase exports and sufficient supply to consumers at reasonable prices. The initiatives include new technology adoption, R&D in feed production, and improve surveillance for disease free poultry production, in particular adoption of good agricultural practices. On top of these, the industry requires better market information system, effective risk management system, and social safety nets.